Scientometric analysis of Radiology, Nuclear Medicine and Medical Imaging publications of Iran in the Web of Science and Scopus Databases - Esmaeilpour-Bandboni, Mohammad; Alizadeh, Iman; YektaKooshali, Mohammad Hossein; Ramezani, Aboozar (Archives of Advances in Biosciences, 2018)
Scientometric analysis should be given great heed in university and research centers for various research and educational reasons. This study aimed to carry out a scientometirc analysis of Radiology, Nuclear Medicine and Medical Imaging articles authored by Iranian researchers and published in journals indexed in the Web of Science and Scopus databases from 2001 to 2016. This is a cross-sectional descriptive study in which as many as 3335 documents authored by Iranian researchers were identified on the two citation databases using field-specific keywords. HistCite™, MS Excel and VOSviewer™ were used to analyze the data. The study discovered that in terms of publications in both citation databases, Iran is almost among the top 30 countries in quantitative and qualitative studies. Iran's contribution was, however, very low in both web of Science (0.32%) and Scopus (0.52%). It was found that “Iranian Journal of Radiation Research” and “Iranian Journal of Radiology” are indexed in both databases; Tehran University of Medical Sciences and University of Tehran are also the most contributing institutions in the databases. According to the findings of the study, it is recommended that Iranian researchers increase their scientific cooperation with researchers from other leading countries in these fields including the United States, Japan and Germany to gain a better quantity and quality of publications.